Lymphofollicular lesions associated with monkeypox (Mpox) virus proctitis. (May 2023) - Mazzotta, Valentina; Scorzolini, Laura; Falasca, Laura; Lionetti, Raffaella; Aguglia, Camilla; Kontogiannis, Dimitra; Colombo, Daniele; Colavita, Francesca; De Palo, Maria Grazia; Carletti, Fabrizio; Mondi, Annalisa; Pinnetti, Carmela; et al.
Highlights: Monkeypox (Mpox) virus has been recently recognized as a cause of proctitis in men who have sex with men. Mpox proctitis may lead to hospitalization for severe anorectal pain. Sigmoidoscopy showed inflamed and friable mucosa, ulcerations, and granular areas. Rectal biopsies revealed for the first time progressive transformation of germinal centers associated with Mpox proctitis. Careful diagnostic workouts and follow-ups are indicated in Mpox proctitis. Abstract: In the recent 2022 monkeypox (Mpox) global outbreak, cases have been mostly documented among men who have sex with men. Proctitis was reported in almost 14% of cases. In this study, four Mpox-confirmed cases requiring hospitalizations for severe proctitis were characterized by clinical, virological, microbiological, endoscopic, and histological aspects. The study showed the presence of lymphofollicular lesions associated with Mpox virus rectal infection for the first time.